Exosomes: Key Messengers Mediating the Interaction Between Tumor Cells and CD8+ T Cells in the Tumor Microenvironment - Li Y; Yang Q; Li D; Li W; Men W (International Journal of Nanomedicine)
Yilin Li,1,* Qiwei Yang,1,* Danni Li,2 Wenya Li,1 Wanfu Men1 1Department of Thoracic Surgery, the First Hospital of China Medical University, Shenyang, 110002, People’s Republic of China; 2Department of Medical Oncology, the First Hospital of China Medical University, Shenyang, 110002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wanfu Men; Wenya Li, Email 472581624@163.com; saint5288@hotmail.comAbstract: In recent years, with an increasingly profound comprehension of the tumor microenvironment, it has been discovered that the constituent cells within the immune microenvironment, such as macrophages, CD4+T cells, and CD8+T cells, interact with tumor cells in manners conducive to tumorigenesis and progression. Exosomes play a pivotal role as essential mediators for intercellular material exchange and signal transmission in this context. Tumor cell-derived exosomes carrying cargo such as PD-L1 and ncRNAs engage with CD8+T cells to induce cytotoxic responses and facilitate immune evasion, thereby promoting tumor advancement. When combined with current immune checkpoint inhibitors like anti-PD-L1/PD-1 therapy, enhancing CD8+T cell function through exosomal pathways while monitoring and augmenting therapeutic effects can significantly improve efficacy. This review delineates the crucial role of exosomes derived from both tumor cells and CD8+T cells within the tumor microenvironment along with their impact mechanisms on both tumor cells and CD8+T cells. Furthermore, it summarizes the potential for clinical treatment in this realm when integrated with existing immunotherapy methods—particularly exploring the feasibility of clinical translation alongside engineering materials science techniques.Keywords: CD8+T, TME, exosome, EVs